Hidden carriers: multidrug-resistant bacteria in hedgehogs from a wildlife rescue centre - Masarikova, Martina; Papouskova, Aneta; Cejkova, Darina; Partovi Nasr, Minoo; Sukkar, Iva; Cizek, Alois (Frontiers in Veterinary Science, 2026)
IntroductionAntimicrobial resistance (AMR) represents a growing One Health challenge at the human–animal–environment interface. Wildlife rescue centres may represent potential, underrecognized settings where resistant bacteria could emerge and disseminate due to close human–animal contact and antimicrobial use. We investigated AMR profiles and genomic features of Escherichia coli isolated from European and northern white-breasted hedgehogs (Erinaceus europaeus, Erinaceus roumanicus) admitted to a Czech wildlife rescue facility.Materials and methodsFaeces from 23 hedgehogs were collected during routine pen cleaning. E. coli isolates were obtained on MacConkey agar (MCA) and MCA with cefotaxime and confirmed by MALDI-TOF MS. Antimicrobial susceptibility to 13 antibiotics was assessed using the disc diffusion test. A subset of 26 isolates representing diverse resistance profiles was further characterised by whole-genome sequencing (WGS). Genomic analyses focused on sequence types, phylogroups, resistance genes, plasmid replicons, and virulence-associated genes.Results and discussionMore than half of the isolates (37/69; 54%) were multidrug-resistant, with resistance most frequently observed to ampicillin and nalidixic acid. No cefotaxime-resistant isolates or genes encoding extended-spectrum beta-lactamases or carbapenemases were detected. Whole-genome sequencing revealed substantial genetic diversity, including several sequence types that are commonly associated with human and animal infections, such as ST457, ST162, and ST624. Isolates carried a wide range of resistance determinants, including blaTEM-1 and qnrB2 genes, plasmid replicons, and virulence-associated genes, with phylogroup F showing the highest virulence gene content. Despite the modest sample size, our findings indicate that hedgehogs in rehabilitation settings can act as reservoirs of multidrug-resistant E. coli with diverse genomic backgrounds, contributing to the environmental dissemination of AMR. The presence of sequence types and resistance genes commonly associated with human and veterinary infections further supports the relevance of rehabilitated wildlife to the broader epidemiology of AMR. Enhancing biosafety practices and antimicrobial stewardship in wildlife rescue operations is therefore essential to mitigate zoonotic risks within a One Health framework.